1999
DOI: 10.1002/hep.510300307
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in pulmonary hemodynamics during intravenous epoprostenol (prostacyclin): A study of 15 patients with moderate to severe portopulmonary hypertension

Abstract: Pulmonary hypertension associated with increased pulmonary vascular resistance (PVR) and occurring in the setting of portal hypertension is referred to as ''portopulmonary hypertension.'' Intravenous epoprostenol (prostacyclin) is a potent pulmonary and systemic vasodilator with antithrombotic properties. It can decrease PVR and pulmonary artery pressure in patients with primary (idiopathic) pulmonary hypertension. Using right-heart catheterization, we evaluated the acute pulmonary hemodynamic effects of intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
166
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(178 citation statements)
references
References 23 publications
5
166
0
7
Order By: Relevance
“…In keeping with previously established criteria, the diagnosis of portopulmonary hypertension was based on the association of a MPAP above 25 mm Hg, a PCWP below 15 mm Hg, and PVR over 120 dynes.s.cm Ϫ5 . 4,7,8 Splanchnic Hemodynamics at Time of Pretransplantation Evaluation. Splanchnic hemodynamic measurements were performed immediately after right heart catheterization using the same vascular access.…”
Section: Methodsmentioning
confidence: 99%
“…In keeping with previously established criteria, the diagnosis of portopulmonary hypertension was based on the association of a MPAP above 25 mm Hg, a PCWP below 15 mm Hg, and PVR over 120 dynes.s.cm Ϫ5 . 4,7,8 Splanchnic Hemodynamics at Time of Pretransplantation Evaluation. Splanchnic hemodynamic measurements were performed immediately after right heart catheterization using the same vascular access.…”
Section: Methodsmentioning
confidence: 99%
“…8 They showed that an acute challenge with intravenous epoprostenol significantly improved pulmonary hemodynamics (reductions in PVR and MPAP and an increase in CO), indicating some acute vasoreactivity was present. Acutely, 79% of patients had greater than a 20% decrease in PVR, and 43% of patients had a 20% decrease in MPAP.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,14 It is unknown how long epoprostenol infusion should be continued after OLT. PPHTN does not reverse immediately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term treatment with epoprostenol, both preoperatively and postoperatively, seems to be efficacious in some patients. 17 The more extensive data being collected in the multicenter database may shed more light on the proper management of this small patient population. 18 …”
mentioning
confidence: 99%